2016
DOI: 10.4014/jmb.1602.02042
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Proteome Profiling of Bacillus pumilus SCU11 Producing Alkaline Protease for Dehairing

Abstract: is one of the most characterized microorganisms that are used for high-level production of select industrial enzymes. A novel SCU11 strain possessing high alkaline protease activity was obtained in our previous work. The culture supernatant of this strain showed efficient dehairing capability with minimal collagen damage, indicating promising potential applications in the leather industry. In this study, the strain's extracellular proteome was identified by LC-MS/MS-based shotgun proteomic analysis, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Excellent hair removal efficiency with proteinases from bacteria such as B. mojavensis SA has been reported ( Hammami et al, 2018 ). Similar properties have likewise been established in Bacillus aerius NSMk2 ( Bhari et al, 2019 ), Bacillus thuringiensis ( Agasthya et al, 2013 ), B. pumilus SCU11 ( Wang et al, 2016 ), Bacillus sp., SB12 ( Briki et al, 2016 ), and B. subtilis KT004404 ( Rehman et al, 2017 ).…”
Section: Bacillary Enzymes In Agriculturesupporting
confidence: 70%
“…Excellent hair removal efficiency with proteinases from bacteria such as B. mojavensis SA has been reported ( Hammami et al, 2018 ). Similar properties have likewise been established in Bacillus aerius NSMk2 ( Bhari et al, 2019 ), Bacillus thuringiensis ( Agasthya et al, 2013 ), B. pumilus SCU11 ( Wang et al, 2016 ), Bacillus sp., SB12 ( Briki et al, 2016 ), and B. subtilis KT004404 ( Rehman et al, 2017 ).…”
Section: Bacillary Enzymes In Agriculturesupporting
confidence: 70%
“…Previously, AprE, Epr, WprA, and Vpr were identified to be extracellular protease in B. pumilus SCU11 [57]. Our transcriptome data indicated that the expression patterns of various extracellular proteases were different in B. pumilus (Table 3).…”
Section: Discussionmentioning
confidence: 63%
“…For example, AprE, Vpr, and aprX may be secreted via this system [63]. However, 65 proteins were detected from the late exponential growth cultures in B. pumilus ; this number is much lower than the predicted protein species (513) [57]. Therefore, the Sec-dependent protein secretion system may be the major pathway, especially during the stationary growth phase in B. pumilus .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proteases control the activation, synthesis, and turnover of proteins to regulate physiological processes (Rawlings et al 2004), which explains the high number of isolates found (Bacillus, Brevibacillus, Microbacterium, Oxalicibacterium-59%) with proteolytic ability, the majority being Bacillus sp. Many authors cited this genus as a producer of alkaline proteases (active at alkaline pH ranging from 9 to 11), which are vital for industrial biocatalysis (Singhal et al 2012;Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%